Advances of Molecular Targeted Therapy in Squamous Cell Lung Cancer - Li MA; Shucai ZHANG (Chinese Journal of Lung Cancer, 2013)
Squamous cell lung cancer (SQCLC) is one of the most prevalent subtypes of lung cancer worldwide, about 400,000 persons die from squamous-cell lung cancer around the world, and its pathogenesis is closely linked with tobacco exposure. Unfortunately, squamous-cell lung cancer patients do not benefit from major advances in the development of targeted therapeutics such as epidermal growth factor receptor (EGFR) inhibitors or anaplastic lymphoma kinase (ALK) inhibitors that show exquisite activity in lungadenocarcinomas with EGFR mutations or echinoderm microtubule associated protein like-4 (EML4)-ALK fusions, respectively. Major efforts have been launched to characterize the genomes of squamous-cell lung cancers. Among the new results emanating from these efforts are amplifications of the fibroblast growth factor receptor 1 (FGFR1) gene, the discoidin domain receptor 2 (DDR2) gene mutation as potential novel targets for the treatment of SQCLCs. Researchers find that there are many specific molecular targeted genes in the genome of squamous-cell lung cancer patients. These changes play a vital role in cell cycle regulation, oxidative stress, cell apoptosis, squamous epithelium differentiation, may be the candidate targeted moleculars in SQCLCs. Here, we provide a review on these discoveries and their implications for clinical trials in squamous-cell lungcancer assessing the value of novel therapeutics addressing these targets.